A Novel Antibiotic Spacer for Significant Proximal Femoral Loss - Surgical Technique - Shields, David (Open Orthop J, 2017)
BACKGROUND: Infections of proximal femora with prosthetic implants in situ have long been a major concern in orthopedic surgery. The gold standard in the management of infected proximal femurs in the presence of prosthetic implants has traditionally been a two-stage revision. However, this is challenging in the setting of extensive bone loss. METHODS: A 3 case series of such infections leading to extensive loss of the proximal femur is presented. We specifically describe our technique of debriding the infected segments as well as utilization of a trochanteric slide osteotomy to resect the femur.We also demonstrate preparation of the “pseudoacetabulum” and femoral component with an antibiotic spacer. CONCLUSION: The high cost of such a procedure is offset by reduction in time spent in hospital. The spacer also helps to allow mobilization by partial weight bearing on a stable femoral component and provide pain control which improves quality of life as compared to prolonged intravenous antimicrobial therapy.